Speech genre of greeting as a marker of mentality (the case of greeting rituals among Russians and Tuvans) - Cherkashina, Tatiana T.; Novikova, Natalia S.; Pugachev, Ivan A. (The New Research of Tuva, 2023)
The article presents an analysis of the greeting ceremony as a model of mentally conditioned speech behavior which has a deep linguoculturological, philosophical content and includes a specific ethnically-marked system that reflects the nominative and semiotic function of the speech genre of greeting with a demonstration of the communicative role of speakers. The speech genre of greeting as a part of speech etiquette is an integral part of the unwritten set of rules that developed during the formation of preferences of ethnic traditions. It determines the choice of forms of expression in typical communication situations. Therefore, it is particularly interesting and important to study the models of human interaction in historical retrospect. This allows us to consider the features of people’s use of specific linguistic and non-linguistic units related to ethnically specific markers of ethicality, emotionality and mentality.This is what determined the objectives of the research: conducting a synchronous and diachronic analysis of greeting rituals in Slavic and Tuvan cultures as a specific speech genre, determining its place and role in the system of ethnocultural preferences of members of both ethnic cultures, as well as comparing the variability of greeting forms which are based on a specific spiritual and moral style of communication, thinking and behavior. A special emphasis in the article is provided on attention to the studies of Tuvan etiquette that has absorbed the unity of the spiritual and the material, the uplifting and spiritualizing principle in the dialogue of man with the natural world. This acts as a kind of vector of human relations, one of the ways for the development of their moral and cultural guidelines that regulate the value choice of people.The results of the study have revealed the historical commonality of many forms of greeting in Russian and Tuvan cultures and have shown that the greeting ritual undergoes changes in the lexical content of speech acts, which make up the etiquette forms of greeting, towards less formal lexical units. At the same time, the article analyzes both verbal and non-verbal forms of greetings that serve to harmonize interpersonal communication. In the conclusion, it is pointed out that despite the global changes experienced by the modern world — active axiological transformations, new sociocultural realities — speech acts of greeting still retain the most vivid cultural preferences and ethnic traditions of using linguistic units.
Keywords: Tuvan culture; Russian culture; communication; speech genre; greeting; ritual; speech etiquette; ethnic traditions